Day-to-Day Living Expenses and Mental Health - Margareta Dackehag; Lina Maria Ellegård; Ulf-G. Gerdtham; Therese Nilsson (Lund University, School of Economics and Management, Department of Economics, 2016)
We use rich longitudinal survey and register data on Swedish individuals to examine the relationship between financial strain and mental health. Specifically, we consider the longitudinal relationships between payment difficulties and subjective (self-reported anxiety) as well as objective (psychiatric drug use) measures of mental ill-health. Among previously healthy individuals, payment difficulty experiences are strongly associated with self-reported mental ill-health. The association with later psychiatric drug use is weaker and differs by gender. Psychiatric drug users are on the other hand at high risk of later experiencing payment difficulties. This indicates that policy measures regarding the payment difficulties–health nexus ought to prioritize activities improving mental health.
Keywords: I12; I30; I31; 330; financial strain; mental health; stress